Cultivating cultural-values in the community development formal learning: The experience of Malaysia in tackling rural poverty - Abdul Aziz, Abdul Rahman (2008)
The accepted wisdom of education as the socializing agent and as the transmitter of cultural-values still prevails. This paper will discover the role of community base education which is formal learning in the “Dewan Orang Ramai” (Community Hall) and “Surau” (place of Muslim worships) in the village. The purpose of the learning was to cultivate cultural-values which were congruent to the demands of development and modernization. Besides that, the community base education also inculcates Islamic values which were relevant and not in conflict with the dominant belief holds by the community concerned. This formal learning was established by the Malaysian Government as a form of intervention to break the vicious circle of poverty. Poverty was widespread in the rural areas but through Government's intervention the younger generation could be drawn out to receive better education, better employment, better training in farming technique and etc. Thus, in a way it looks like giving the education to the village folks, but the deeper meaning it will have a snow-ball effect for the next generation. The Government agency which in particular runs the function was established in 1961. It was and still known as KEMAS or “Jabatan Kemajuan Masyarakat” or Department of Social Development under the stewardship of Ministry of Rural Development.